The Description Of Knowledge And Attitude Of Flood Disaster Preparedness Of Residents In Kwarasan Sub-District - Rahmawati, Diah Nur; Prajayanti, Eska Dwi (Jurnal Kegawatdaruratan Medis Indonesia, 2023)
Flood is a natural phenomenon triggered by natural processes and uncontrolled human activity. In early 2023, flooding in Kwarasan Sub-District occurred twice in January and February which were the worst floods after 2007. Knowledge and attitude of preparedness are important things to have because knowledge of disaster preparedness will affect a person's attitude when a disaster occurs, which be used in the long term to minimize the impact of the disaster. This research aims to know the description of the knowledge and attitude of flood disaster preparedness of residents in Kwarasan, Grogol, Sukoharjo. The type of research used is a quantitative description with survey methods. The sample in this research was 78 heads of families in the Kwarasan sub-district using purposive sampling and stratified random sampling techniques. The results of the research on preparedness knowledge were in the good category with 76 (97.4%) respondents and 2 (2.6%) respondents in the sufficient category. Then the results of the research on preparedness attitudes were in the good category with 61 (78.2%) respondents and 17 (21.8%) respondents in the sufficient category. The Conclusion is the description of the knowledge and attitude of flood disaster preparedness is mostly in the good category.